Motivasi Kerja Karyawan dalam Kajian Teori Kebutuhan Maslow - Arni Utama Ningsih; Gustria Monika; Yenida Yenida (Jurnal Ilmiah Poli Bisnis, 2019)
This research is a quantitative study based on Maslow's theory of needs. This study involved 40 respondents from the human resources division at PT BNI Syariah South Jakarta Central Office. This study provides evidence of Maslow's theory of needs that can be applied to the workplace. The results of the study stated that physiological needs, safety and security, affiliation or acceptance needs, Esteem needs, and self-actualization needs dominantly influenced the motivation of BNI Syariah employees at the South Jakarta Head Office.